Tracing blood units to their recipients: results of a two-centre study. - Ballard, S; Buck, J; Llewelyn, C; Murphy, M; Williamson, L (2003)
An important principle of the use of blood components is the ability to trace them from the donor to the recipient. This study set out to establish whether there was sufficient documentation in patient case notes to confirm the transfusion of blood components in a sample of computer blood bank records at two large teaching hospitals in UK. The criteria for verification of transfusion were taken from guidelines from the British Committee for Standards in Haematology (Transfusion Medicine 1999, 9, 227-238). The blood bank computer records indicated that 486 units of blood components were issued and not returned to the blood bank for 80 patients during a 2-month period. Of the 486 units, transfusion of 409 units (84%) was verified against patient notes, but 77 units (16%) could not be verified as received by the patient. The study showed that documentation of transfusions was variable. For example, written prescriptions were only found for 204 units (42%). These results have implications for 'lookback studies' involving blood transfusion. Further efforts are required to educate those involved in transfusing blood about the need for accurate documentation.